(untitled) (Research, Society and Development, 2025)
Dermatological diseases are among the main causes of veterinary consultations in dogs, significantly affecting their health, well-being, and the daily routine of their owners. In recent years, interest has grown in the relationship between the gut microbiota and skin health, particularly regarding the influence of dysbiosis on the immune system and the development of conditions such as atopic dermatitis. This study aims to review the scientific literature on the use of gut microbiota modulation through probiotics, prebiotics, and fecal microbiota transplantation as a therapeutic strategy in the treatment of dermatological diseases in dogs. For this purpose, a bibliographic search was conducted in the SciELO and Google Scholar databases, prioritizing articles published between 2008 and 2024. The reviewed studies indicate that microbiota modulation may contribute to improving intestinal homeostasis and immune response, with positive effects on skin health. It is concluded that the gut microbiota has promising potential as an adjuvant therapy in veterinary dermatology, although further clinical studies are needed to confirm its efficacy and standardize treatment protocols.